Case Report: Anti-neural cell adhesion molecule 1 antibody-positive encephalitis presenting with schizophrenia-like symptoms and an ovarian teratoma - Yamanaka, Nanami; Honda, Masaya; Shiwaku, Hiroki; Toyoda, Saori; Motokawa, Yukiko; Hara, Makoto; Tomita, Shusaku; Shimizu, Fumitaka; Koga, Michiaki; Nakamori, Masayuki (Frontiers in Immunology, 2026)
Autoimmune encephalitis (AE) has been linked to various autoantibodies, with anti-neural cell adhesion molecule 1 (NCAM1) antibodies recently identified in patients with schizophrenia. Their pathogenic potential has been demonstrated in passive transfer experiments in mice. We report the first case of AE associated with anti-NCAM1 antibodies in a 15-year-old female who presented with acute-onset psychiatric symptoms, including delusions, hallucinations, and catalepsy, along with fever and impaired consciousness. Cerebrospinal fluid analysis showed a high IgG index, and electroencephalography revealed generalized slow-wave activity. However, brain magnetic resonance imaging was unremarkable. A pelvic tumor was identified, and adnexectomy confirmed a right mature cystic teratoma. Given the clinical presentation, anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis was initially suspected, and the patient was treated with intravenous methylprednisolone and intravenous immunoglobulin, resulting in significant improvement. Despite a subsequent relapse of hallucinations, additional immunotherapy led to complete resolution of symptoms. Notably, anti-NMDAR and other well-known neuronal surface antibodies were negative in both serum and cerebrospinal fluid, whereas anti-NCAM1 antibodies were detected. Immunohistochemical analysis confirmed NCAM1 expression in the excised ovarian tissue, and post-treatment serum tests showed the disappearance of anti-NCAM1 antibodies. The concurrent resolution of clinical symptoms and the disappearance of these antibodies support their pathogenic role. The clinical presentation and paraneoplastic association with teratoma closely resemble anti-NMDAR encephalitis, suggesting that anti-NCAM1 antibodies may define a novel form of AE with psychotic manifestations. Further research is needed to clarify their role in neuroinflammatory disorders.